2004
DOI: 10.1152/jn.01132.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Features of Odorants Systematically Influence Slow Temporal Responses Across Clusters of Coordinated Antennal Lobe Units in the MothManduca sexta

Abstract: Behavioral studies of olfactory discrimination and stimulus generalization in many species indicate that the molecular features of monomolecular odorants are important for odor discrimination. Here we evaluate how features, such as carbon chain length and functional group, are represented in the first level of synaptic processing. We recorded antennal lobe ensemble responses in the moth Manduca sexta to repeated 100-ms pulses of monomolecular alcohols and ketones. Most units exhibited a significant change in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
79
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 80 publications
11
79
0
Order By: Relevance
“…Early studies (15,19) indicated that the MBs play a critical role in olfactory memory and suggested that olfactory memories are formed upstream of the output neurons of the MBs, which determine performance, and that the memory trace probably lies within the MBs. More recently, studies using food or electric shock as a US in a variety of insects, including bees (38), flies (39), and moths (20), have shown that learning-dependent changes in neural activity also occur as early as the antennal lobe, which therefore appears to be the first site in the olfactory pathway for convergence of the conditioned stimuli and US and thus may be a site for the circadian regulation of memory acquisition in the cockroach. US pathways that lead to this convergence are not well understood; however, there are data that suggest that aminergic input may play a pivotal role.…”
Section: Memory Acquisition Vs Memory Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies (15,19) indicated that the MBs play a critical role in olfactory memory and suggested that olfactory memories are formed upstream of the output neurons of the MBs, which determine performance, and that the memory trace probably lies within the MBs. More recently, studies using food or electric shock as a US in a variety of insects, including bees (38), flies (39), and moths (20), have shown that learning-dependent changes in neural activity also occur as early as the antennal lobe, which therefore appears to be the first site in the olfactory pathway for convergence of the conditioned stimuli and US and thus may be a site for the circadian regulation of memory acquisition in the cockroach. US pathways that lead to this convergence are not well understood; however, there are data that suggest that aminergic input may play a pivotal role.…”
Section: Memory Acquisition Vs Memory Retrievalmentioning
confidence: 99%
“…Olfactory learning in insects, in particular, is widespread and has been extensively used as a model for studies on the behavior, neurobiology, genetics, and molecular biology of learning and memory in bees (e.g., 16,17), fruit flies (15,18,19), and moths (20). As a consequence, much is understood about the anatomical substrate and physiological and molecular mechanisms of insect olfactory learning.…”
mentioning
confidence: 99%
“…We have shown that plasticity in the AL acts to increase separation of patterns evoked by odors that have been differentially associated with food (Fernandez et al, 2009). However, research on olfactory coding and plasticity has focused on pure odors or simpler mixtures (Daly et al, 2004;Fernandez et al, 2009;Stopfer et al, 2003;Deisig et al, 2006Deisig et al, , 2010Guerrieri et al, 2005;Linster and Smith, 1999) rather than on the more complex odor problems presented by flowers. Even when more complex odor mixtures were used, odor compositions were not systematically varied as odors would vary from flower to flower of the same species in natural scenes.…”
Section: Introductionmentioning
confidence: 99%
“…Correlate specific electrical impulses to the activity of single neurons. Follow spike sorting procedures laid out in detail elsewhere 10,14,18 . Use the program KlustaKwik (version 1.5, author K. Harris, Rutgers University) to generate initial, automated clustering.…”
Section: Methodsmentioning
confidence: 99%